INDIVIDUALISM IN THE 1997 ANIMATED FILM ANASTASIA: A LIBERAL FEMINISM PERSPECTIVE - Alfarras, Riziq Prio; Purwarno, Purwarno (Universitas Muhammadiyah Lampung, 2024)
This research aims to analyze how Anastasia portrays themes of liberal feminism and individualism. It investigates how the protagonist’s journey embodies feminist ideals of self-discovery, resilience, and the defiance of gender expectations. Grounded in liberal feminist theory, which emphasizes personal autonomy and equality before the law (McMillan, 2009); this study employs qualitative descriptive methods to explore how Anastasia’s narrative reflects these principles. Themes such as identity formation, gender norms, and personal agency are analyzed through the protagonist’s experiences. The analysis reveals that Anastasia challenges traditional gender roles by portraying feminine traits—compassion, resilience, and emotional intelligence—as strengths rather than weaknesses. The protagonist’s journey from orphaned amnesiac to rediscovered princess illustrates themes of empowerment and self-determination within a feminist framework. The film’s depiction of Anastasia’s relationships and challenges underscores the broader feminist discourse on identity and societal expectations. By confronting external pressures and embracing her true self, Anastasia embodies the resilience and agency central to feminist ideals. Through its narrative complexity and thematic depth, Anastasia contributes meaningfully to feminist discourse. It celebrates personal growth; challenges gender stereotypes, and advocates for women’s empowerment. The study concludes with reflections on the enduring relevance of feminist themes in animated media and their impact on audiences.